Study of O-Phosphorylation Sites in Proteins Involved in Photosynthesis-Related Processes in Synechocystis sp Strain PCC 6803: Application of the SRM Approach - Angeleri M; Muth-Pawlak D; Aro EM; Battchikova N (AMER CHEMICAL SOC, 2022)
O-Phosphorylation has been shown in photosynthesis related proteins in a cyanobacterium Synechocystis sp. strain PCC 6803 (thereafter Synechocystis 6803), suggesting that phosphorylation of S, T, and Y residues might be important in photosynthesis-related processes. Investigation of biological roles of these phosphorylation events requires confident knowledge of the phosphorylated sites and prospects for their individual assessment. We performed phosphoproteomic analysis of Synechocystis 6803 using TiO2 enrichment of the phosphopeptides, followed by LC-MS/MS, and discovered 367 phosphorylation sites in 190 proteins participating in various cellular functions. Furthermore, we focused on the large group of phosphoproteins that are involved in light harvesting, photosynthesis driven electron flow, photoprotection, and CO2 fixation. The SRM approach was applied to verify/improve assignments of phosphorylation sites in these proteins and to investigate possibilities for analysis of phosphopeptide isomers. The SRM assays were designed for peptides comprising 45 phosphorylation sites. The assays contain peptide iRT values and Q1/Q3 transitions comprising those discriminating between phosphopeptide isoforms. The majority of investigated phosphopeptides and phosphorylated isoforms could be individually assessed with the SRM technique. The assays could be potentially used in future quantitative studies to evaluate an extent of phosphorylation in photosynthesis related proteins in Synechocystis 6803 cells challenged with various environmental stresses.